Negative electrode material, preparation method of negative electrode material, negative electrode plate, battery and electric device

By using negative electrode materials without the additives such as graphite and carbon nanotubes in lithium iron phosphate batteries, the battery structure is optimized, and the problem of poor capacity attenuation and circulation performance of traditional lithium iron phosphate batteries at high temperatures is solved, and the high temperature environment is achieved Improved long cycle performance.

CN119208597APending Publication Date: 2024-12-27GREE ALTAIRNANO NEW ENERGY INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411167483.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional lithium iron phosphate batteries have fast capacity decays and poor circulation performance in high-temperature environments, making it difficult to meet the application needs in high-temperature environments.

Method used

Using negative electrode materials including uncovered graphite, conductive agent, binder and specific additives, the additives include carbon nanotubes and conductive polymers. By optimizing the combination of graphite particle size and additives, a high-temperature battery is prepared to increase the high temperature of the battery. Long cycle performance.

Benefits of technology

Cycling at 45°C for 2000 weeks, the battery capacity retention rate remains above 84%, significantly improving the battery's cycle life and high-temperature performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005008271910000051
    Figure BDA0005008271910000051
  • Figure BDA0005008271910000061
    Figure BDA0005008271910000061
  • Figure HDA0005008271920000011
    Figure HDA0005008271920000011
Patent Text Reader

Abstract

The invention relates to the field of batteries, and discloses a negative electrode material and a preparation method thereof, a negative electrode plate, a battery and an electric device. The negative electrode material comprises graphite, a conductive agent, a binder and an additive, the D50 of the graphite is 12-20 microns, the graphite is not coated, and the additive comprises one or more than two of a carbon nanotube and a conductive polymer. The high-temperature long-cycle performance of the battery is improved by optimizing the negative electrode material, specifically, the particle size and the coating state of graphite are optimized, and a specific additive is added into the negative electrode material, so that the high-temperature battery is prepared, the battery capacity retention rate is still kept at 84% or above after the battery is cycled for 2000 weeks at the high temperature of 45 DEG C, and the service life of the battery is prolonged. The cycle life and the high-temperature performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a negative electrode material and a preparation method thereof, as well as a negative electrode sheet, a battery and an electrical device. Background Art

[0002] At present, lithium-ion batteries have been widely used as an important energy source. Whether in the field of electronic communications or in the field of transportation, they play an extremely important role and have broad application prospects. Lithium-ion batteries have high operating voltage, high specific energy, large capacity, low self-discharge, good cycle performance, long service life, light weight and small size. They are the representative of modern high-performance batteries.

[0003] With the rapid development of new energy vehicles, the performance requirements for power batteries are getting higher and higher. Especially in high temperature environments, the performance and safety of batteries have received widespread attention. Commercial lithium-ion power batteries can be divided into soft-pack batteries, cylindrical batteries, square metal shell batteries, etc. according to size specifications and packaging types. Lithium-ion battery positive electrode materials are mainly divided into nickel-cobalt-manganese (aluminum) ternary materials, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, etc. Among them, nickel-cobalt-manganese (aluminum) ternary materials and lithium cobalt oxide materials have higher specific capacity, but they contain precious metals nickel and cobalt, so their material costs are relatively high. In addition, due to the strong oxidizing properties of high-priced nickel and cobalt, the safety of nickel-cobalt-manganese (aluminum) ternary materials and lithium cobalt oxide materials is poor, and batteries made from them are difficult to pass safety tests such as acupuncture and overcharging. Materials such as lithium manganese oxide, lithium iron phosphate and lithium manganese iron phosphate are cheaper because they do not contain precious metals, and the safety of such materials is also better.

[0004] At present, lithium iron phosphate batteries are widely used in electric vehicles and other fields due to their safety, stability, and environmental protection. However, the capacity of traditional lithium iron phosphate batteries decays rapidly and the cycle performance is poor in high temperature environments, making it difficult to meet the application requirements in high temperature environments. Therefore, developing a high-temperature lithium iron phosphate battery to improve its performance and cycle life in high temperature environments has important practical significance and application value. Summary of the invention

[0005] In view of this, the purpose of the present application is to provide a negative electrode material and a preparation method thereof, so that the negative electrode material can significantly improve the high temperature and long cycle performance of the battery;

[0006] Another object of the present application is to provide a negative electrode sheet, a battery and an electrical device based on the above-mentioned negative electrode material.

[0007] In order to solve the above technical problems / achieve the above objectives or at least partially solve the above technical problems / achieve the above objectives, as a first aspect of the present application, a negative electrode material is provided, comprising graphite, a conductive agent, a binder and an additive; the graphite has a D 50 The nanostructured carbon nanotube has a diameter of 12 to 20 μm and is not coated. The additive comprises one or more of carbon nanotubes and conductive polymers.

[0008] Optionally, the additive is added in an amount of 0.5-2% of the mass of graphite.

[0009] Optionally, the conductive polymer includes polyaniline and polypyrrole.

[0010] As a second aspect of the present application, a method for preparing the negative electrode material is provided, wherein the additive is uniformly mixed with graphite, and then mixed with a binder, a conductive agent, and a solvent in proportion to form a negative electrode slurry, and the negative electrode material is obtained after drying.

[0011] As a third aspect of the present application, a negative electrode plate is provided, comprising a current collector and a negative electrode active material coated on at least one surface of the current collector; the negative electrode active material comprises the negative electrode material described in the present application.

[0012] As a fourth aspect of the present application, a battery is provided, comprising the negative electrode plate described in the present application.

[0013] Optionally, it is a lithium-ion battery, comprising a positive electrode plate, a separator, an electrolyte, and the negative electrode plate described in the present application, and the positive electrode active material of the positive electrode plate comprises lithium iron phosphate.

[0014] As a fifth aspect of the present application, an electrical device is provided, comprising the battery described in the present application.

[0015] The present application improves the high-temperature and long-cycle performance of the battery by optimizing the negative electrode material, specifically including optimizing the particle size and coating state of graphite and adding specific additives to the negative electrode material, thereby preparing a high-temperature battery. After 2000 cycles at a high temperature of 45°C, the battery capacity retention rate remains above 84%, thereby improving the cycle life and high-temperature performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application.

[0017] Figure 1 Shown is the high temperature and long cycle curve of the soft-pack battery prepared with the negative electrode material of the present application. DETAILED DESCRIPTION

[0018] The present application discloses a negative electrode material and a method for preparing the same, as well as a negative electrode sheet, a battery and an electrical device. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0019] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.

[0020] In the first aspect of the present application, a negative electrode material is provided, comprising graphite, a conductive agent, a binder and an additive; the graphite has a D 50 The particle size of the graphite is 12 to 20 μm and is not coated, and the additive includes one or more of carbon nanotubes and conductive polymers. For the graphite particle size, too low D50 will produce a larger specific surface, which is not conducive to high temperature cycle performance and will increase the cost of graphite materials. Too high D50 will increase the difficulty of processing and worsen the subsequent process of the battery cell. Usually, the existing graphite is carbon-coated for conductivity, first charge reversible capacity, cycle stability, room temperature cycle performance and rate performance, but during the research process of this application, it was found that there are disadvantages in coating graphite in high temperature and long cycle performance.

[0021] In certain embodiments of the present application, the D 50The specific surface area of ​​the graphite is 1.5-2m 2 / g, too large a specific surface area is not conducive to high temperature and long cycle performance.

[0022] In some embodiments of the present application, the mass percentages of the graphite, the conductive agent, and the binder are 90-98%: 1-5%: 1-5%, on this basis, the additive is added in an amount of 0.5-2% of the mass of the graphite, such as 0.5%, 1%, 1.5% or 2%. In some other embodiments of the present application, the mass percentages of the graphite, the conductive agent, and the binder are 95.2%: 2%: 2.8%.

[0023] In some embodiments of the present application, the conductive polymer includes polyaniline and polypyrrole. In other embodiments of the present application, the additive is carbon nanotubes, or carbon nanotubes + conductive polymers, and the carbon nanotubes are 10 to 30 μm in length and 10 to 50 nm in diameter. In other embodiments of the present application, the additive is polyaniline, or a mixed additive of carbon nanotubes + polypyrrole. More specifically, the additive is any one of the following:

[0024] (1) carbon nanotubes added in an amount of 1% by weight of graphite;

[0025] (2) polyaniline added in an amount of 2% by weight of graphite;

[0026] (3) Carbon nanotubes added in an amount of 0.5% by weight of graphite and polypyrrole added in an amount of 1.5% by weight of graphite.

[0027] In the second aspect of the present application, a method for preparing the negative electrode material is provided, wherein the additive is uniformly mixed with graphite, and then mixed with a binder, a conductive agent, and a solvent in proportion to form a negative electrode slurry, and the negative electrode material is obtained after drying. The conductive agent includes, but is not limited to, one or more of a carbon black conductive agent, a graphene conductive agent, and a carbon fiber conductive agent. The carbon black conductive agent includes conductive carbon black SP, Ketjen black, and acetylene black, etc. The binder includes PVDF, PAA, SBR, CMC, etc. The solvent includes water or an organic solvent, such as NMP.

[0028] In a third aspect of the present application, a negative electrode plate is provided, comprising a current collector and a negative electrode active material coated on at least one surface of the current collector; the negative electrode active material comprises the negative electrode material described in the present application.

[0029] In the process of preparing the negative electrode sheet, the negative electrode slurry is coated on a current collector with good conductivity such as copper foil to form a uniform negative electrode layer. Then, it is dried in a constant temperature drying oven to remove moisture and solvent in the negative electrode layer. The dried negative electrode sheet is roller-pressed to increase its density and compactness. Then, the negative electrode sheet is cut according to the battery design requirements to obtain a negative electrode sheet that meets the requirements.

[0030] In a fourth aspect of the present application, a battery is provided, comprising the negative electrode plate described in the present application.

[0031] In certain embodiments of the present application, it is a lithium-ion battery, including a positive electrode plate, a separator, an electrolyte, and the negative electrode plate described in the present application, and the positive electrode active material of the positive electrode plate includes lithium iron phosphate.

[0032] In certain embodiments of the present application, the lithium-ion battery includes but is not limited to a soft-pack battery, a button battery, a square shell battery, a half-cell or a full battery, etc. In certain embodiments of the present application, a soft-pack lithium-ion battery is provided, wherein the positive electrode sheet active material is composed of lithium iron phosphate, PVDF, and conductive carbon black SP, and the negative electrode sheet active material is respectively composed of the above graphite, conductive carbon black SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR, and the diaphragm adopts a 16μmPP base film. The electrolyte contains 1mol / L LiPF6, EC:EMC:DEC (mass ratio 25:40:30) and VC2%. The negative electrode sheet, the diaphragm and the positive electrode sheet are stacked in a Z shape to form a soft-pack battery, with a designed N / P of 1.15 and a designed capacity of 3Ah.

[0033] In a fourth aspect of the present application, an electric device is provided, comprising the lithium-ion battery described in the present application, wherein the lithium-ion battery provides electric energy for the electric device. The electric device may be various devices or equipment driven by the lithium-ion battery, including but not limited to electric vehicles, electric vehicles, self-balancing vehicles, flatbed vehicles, aircraft, lighting equipment, household appliances, etc.

[0034] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.

[0035] The following is a further description of a negative electrode material and a preparation method thereof, as well as a negative electrode plate, a battery and an electrical device provided in the present application.

[0036] Embodiment 1:

[0037] Lithium iron phosphate raw material: select particle size distribution of 1-5μm and tap density of 0.9-1.3g / cm 3, with a specific surface area of ​​7.5 to 11.3 m 2 / g of carbon-coated lithium iron phosphate material.

[0038] Additives: Carbon nanotubes are selected, with a length of 10 to 30 μm and a diameter of 10 to 50 nm, and the added amount is 1 wt% of the mass of graphite.

[0039] Graphite material: D 50 15μm (uncoated), specific surface area 1.0-2m 2 / g;

[0040] Mixing of additives: Mix the carbon nanotubes and graphite particles evenly in a vacuum mixer to ensure that the carbon nanotubes are evenly dispersed between the graphite particles.

[0041] Preparation of negative electrode slurry: The mixed graphite particles and additives are uniformly mixed with appropriate amounts of binders CMC and SBR and conductive agent conductive carbon black SP in a certain proportion to prepare negative electrode slurry (the mass percentage of graphite, conductive agent and binder is 95.2%:2%:2.8%).

[0042] Coating and drying: The negative electrode slurry is coated on a substrate such as copper foil to form a uniform negative electrode layer. Then, it is dried in a constant temperature drying oven to remove moisture and solvent in the negative electrode layer.

[0043] Rolling and cutting: Roll the dried negative electrode sheet to improve its density and compaction. Then, cut the negative electrode sheet according to the battery design requirements to obtain the negative electrode sheet that meets the requirements.

[0044] The positive electrode sheet is composed of LFP, polyvinylidene fluoride PVDF, conductive carbon black SP (LFP: SP: PVDF = 96%: 1.5%: 2.5%), and the diaphragm uses a 16μm PP base film. The electrolyte contains 1mol / L LiPF6, EC:EMC:DEC (mass ratio 25:40:30) and VC2%. The negative electrode sheet, diaphragm and positive electrode sheet are stacked in a Z shape to make a soft pack battery, with a designed N / P of 1.15 and a designed capacity of 3Ah.

[0045] Embodiment 2:

[0046] Additive: polyaniline is selected, and the addition amount is 2wt% of the mass of graphite.

[0047] The other parts are prepared with reference to Example 1.

[0048] Embodiment 3:

[0049] Additives: A mixed additive of carbon nanotubes (same as in Example 1) and polypyrrole is selected, wherein the amount of carbon nanotubes added is 0.5 wt% of the mass of graphite, and the amount of polypyrrole added is 1.5 wt% of the mass of graphite.

[0050] The other parts are prepared with reference to Example 1.

[0051] Comparative Example 1:

[0052] Graphite material: D 50 10μm (uncoated), specific surface area 1.5-2m 2 / g;

[0053] The other parts are prepared with reference to Example 1.

[0054] Comparative Example 2:

[0055] Graphite material: D 50 15μm (carbon coating), specific surface area 1.5-2m 2 / g; The carbon coating process is: mixing graphite and asphalt, carbonizing at 1250°C to obtain a coated product.

[0056] The other parts are prepared with reference to Example 1.

[0057] Experimental example:

[0058] High temperature cycle performance test method:

[0059] (1) Place at 45°C for 24 hours;

[0060] (2) At high temperature of 45°C, 1C constant current and constant voltage charging to 3.65V, cut-off current 0.05C;

[0061] (3) Leave for 10 minutes;

[0062] (4) At high temperature of 45°C, discharge at 1C constant current to 2.0V;

[0063] (5) Leave for 10 minutes;

[0064] (6) Jump to step 2, end condition: cycle 2000 times

[0065] Results Figure 1 and Table 1;

[0066] Table 1

[0067]

[0068]

[0069] according to Figure 1As shown in Table 1, within a reasonable particle size range, the larger the particle size, the better the high temperature cycle performance of the assembled battery, which can be obtained from the results of Example 1 and Comparative Example 1. At the same time, the difference between Example 1 and Comparative Example 2 is whether the graphite is carbon-coated. According to the results, it can be clearly seen that the high temperature cycle performance after carbon coating is significantly reduced, and the capacity retention rate after 2000 cycles is only 63.81%.

[0070] There are certain differences in the cycle performance between the examples, among which the result of Example 3 is the best, which shows that different additives can affect the high-temperature cycle performance of the battery, and the mixed additive formed by carbon nanotubes and conductive polymers has a better effect.

[0071] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A negative electrode material, characterized in that: It includes graphite, conductive agent, binder and additives; the graphite has a D 50 The nanostructured carbon nanotube has a diameter of 12 to 20 μm and is not coated. The additive comprises one or more of carbon nanotubes and conductive polymers.

2. The negative electrode material according to claim 1, characterized in that The additive is added in an amount of 0.5-2% of the mass of graphite.

3. The negative electrode material according to claim 1, characterized in that The conductive polymer includes polyaniline and polypyrrole.

4. The method for preparing the negative electrode material according to claim 1, characterized in that: After the additive is evenly mixed with graphite, it is mixed with a binder, a conductive agent and a solvent in proportion to form a negative electrode slurry, and the negative electrode material is obtained after drying.

5. A negative electrode plate, characterized in that: It comprises a current collector and a negative electrode active material coated on at least one surface of the current collector; the negative electrode active material comprises the negative electrode material according to any one of claims 1 to 3.

6. A battery, characterized in that: Including the negative electrode sheet as described in claim 5.

7. The battery according to claim 6, characterized in that It is a lithium-ion battery, comprising a positive electrode plate, a separator, an electrolyte, and the negative electrode plate as claimed in claim 5, wherein the positive electrode active material of the positive electrode plate comprises lithium iron phosphate.

8. An electrical device, characterized in that: A battery comprising the battery of claim 6 or 7.